Microcontroller-based Vertical Farming Automation System - Shomefun Tobi Emmanuel; Awosope Claudius O. A.; Ebenezer O. Diagi (Institute of Advanced Engineering and Science, 2018)
Food is a basic necessity of life. It is the means by which man is nourished and strengthened to carry out his daily activities. The need for food for the upkeep of man has placed agriculture at the helm of man’s affairs on earth. With a rapidly increasing population on earth, man has invented newer and innovative ways to cultivate crops. This cultivation is mainly concentrated in rural areas of countries around the world; but with the massive urbanization happening in the world today; it is becoming increasingly difficult to have enough agricultural produce that will cater for the massive population. Taking Nigeria as a case study, the increased urbanization has placed a massive demand on land, energy and water resources within urban areas of the country. Majority of the food consumed in the urban areas is cultivated in the rural areas. This system however requires longer transportation times from rural areas to urban areas which lead to contamination and spoilage in many instances. This research paper provides a solution in which food crops can be cultivated easily in urban areas by planting in vertically stacked layers in order to save space and use minimal energy and water for irrigation.